Do Forecasters Believe in Okun's Law? : An Assessment of Unemployment and Output Forecasts - Ball, Laurence (IMF Working Papers; Working Paper, 2014)
This paper provides an assessment of the consistency of unemployment and output forecasts. We show that, consistent with Okun's Law, forecasts of real GDP growth and the change in unemployment are negatively correlated. The Okun coefficient-the responsiveness of unemployment to growth-from forecasts is fairly similar to that in the data for various countries. Furthermore, revisions to unemployment forecasts are negatively correlated with revisions to real GDP forecasts. These results are based on forecasts taken from Consensus Economics for nine advanced countries since 1989.